Anesthesia Management for Section Cesarean Delivery in Patient with Severe Mitral Stenosis - Fanniyah Fanniyah; Isngadi Isngadi (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2022)
Background: Heart defects in pregnancy is one main nonobstetric factor causing morbidity and mortality in pregnant women. Mitral stenosis is common in pregnancy. The choice of anesthetic management has to consider hemodynamics, type of heart disease, and drugs used. Neuraxial anesthesia has been significantly used because it is considered safer than general anesthesiaCase: A 26-year-old woman with gestational age 32-34 weeks with severe mitral stenosis, moderate mitral regurgitation, severe tricuspid regurgitation, pulmonary hypertension, pericardial effusion, and atrial fibrillation underwent cesarean section with a low dose of spinal anesthesia using 5mg bupivacaine heavy 0.5% and Fentanyl 50 mcg. The sensory and motoric block was achieved in 5 minutes. Hemodynamic was stable during the perioperative phase. There was no heart failure or postoperative hemodynamic deterioration.Conclusion: Low-dose spinal anesthesia using 5 mg of bupivacaine and fentanyl adjuvant can be used in cesarean section in patients with severe mitral stenosis due to rapid onset, adequate block level, stable hemodynamic, block duration, and healthy born babies.Keywords: Pregnancy; mitral stenosis; C-section; neuraxial block; low dose